Behavior of 137Cs Activity in the Sayung Waters, Demak, Indonesia - M Muslim; H. Suseno; M.J. Pratiwi (Atom Indonesia, 2017)
The behavior of anthropogenic radionuclide 137Cs in the water and sediment has been examined with regard to particle size, organic sediment, and other physical conditions in the Sayung estuarine waters of Demak. Previously, this estuary was used as shrimp culture brackish water ponds that were affected by serious erosion and intrusion. Furthermore, this regency rapidly industrialized over the last three decades. The activities of 137Cs in the six stations in water and sediment were in the 0.0116-0.4509 mBq/L and 0.3747-1.2442 Bq/kg ranges with mean activities of 0.2278 mBq/L and 0.8594 Bq/kg, respectively, depending on the prevailing physicochemical regime at the sampling station. The highest activities of aqueous 137Cs occurred in station 2 but the highest in sediment occurred in station 6 located closed to the main land of Sayung. Fast current effectively diluted 137Cs as a conservative radionuclide in seawater, thus the activity of 137Cs in seawater decreased when the current speed increased. This effect was caused in part by industrial pollutants that adsorbed 137Cs and precipitated onto the surface sediment. Organic matters and clay materials in sediment were not significantly effective at binding 137Cs in Sayung waters in the industrial coastal area, but the correlation increased in open areas separated by a breakwater (second group stations) and the location further from the beach or in open sea. This indicates that industrial pollutants are more effective at binding 137Cs than organic matters and clay materials. Fine grain size sediment is also more ineffective at binding 137Cs; it may be caused by the sediment's high total organic matter content.Received: 25 April 2016; Revised: 27 October 2016; Accepted: 8 November 2016